EARLY CRETACEOUS U–PB ZIRCON AGES FOR THE COPIAPó PLUTONIC COMPLEX AND IMPLICATIONS FOR THE IOCG MINERALIZATION AT CANDELARIA, ATACAMA REGION, CHILE - Marschik R.; Söllner F. (My University, 2006)
Four of the major plutons in the vicinity of the Candelaria mine (470 Mt at 0.95% Cu, 0.22 g/t Au, 3.1 g/t Ag) and a dike–sill system exposed in the Candelaria open pit have been dated with the U–Pb zircon method. The new geochronological data indicate that dacite magmatism around 123 Ma preceded the crystallization of hornblende diorite (Khd) at 118 ± 1 Ma, quartz–monzonite porphyry (Kqm) at 116.3 ± 0.4 Ma, monzodiorite (Kmd) at 115.5 ± 0.4 Ma, and tonalite (Kt) at 110.7 ± 0.4 Ma. The new ages of the plutons are consistent with field relationships regarding the relative timing of emplacement. Plutonism temporally overlaps with the iron oxide Cu–Au mineralization (Re–Os molybdenite ages at ~115 Ma) and silicate alteration (ages mainly from 114 to 116 and 110 to 112 Ma) in the Candelaria–Punta del Cobre district. The dated dacite porphyry and hornblende diorite intrusions preceded the ore formation. A genetic link of the metallic mineralization with the quartz–monzonite porphyry and/or the monzodiorite is likely. Both of these metaluminous, shoshonitic (high-K) intrusions could have provided energy and contributed fluids, metals, and sulfur to the hydrothermal system that caused the iron oxide Cu–Au mineralization. The age of the tonalite at 110.7 Ma falls in the same range as the late alteration at 110 to 112 Ma. Tonalite emplacement may have sustained existing or driven newly developed hydrothermal cells that caused this late alteration or modified 40Ar/39Ar and K/Ar systematic in some areas.
Keywords: CANDELARIA-PUNTA DEL COBRE; CHILE; IOCG DEPOSITS; U-PB ZIRCON DATING; Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая